Successful venous thrombectomy for extensive cerebral venous and sinus thrombosis after failed diagnostic lumbar puncture - Döring, Katja; Ratuszny, Dominica; Schuppner, Ramona; Giesemann, Anja; Bültmann, Eva; Lanfermann, Heinrich; Abu-Fares, Omar (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
With an incidence of 2–5 per million adults, cerebral venous and sinus thrombosis (CVST) is a rarity in the spectrum of cerebrovascular diseases. The etiology and symptomatic presentation are heterogeneous and diverse. CSVT is, therefore, often underdiagnosed. In addition to therapeutic anticoagulation, venous thrombectomy is a last-resort therapy in individual cases.A 42-year-old woman was admitted to the hospital with postural headache following an unsuccessful lumbar puncture. On suspicion of post-puncture syndrome, analgesic therapy with adjuvant caffeine tablets was initially chosen, leading to rapid improvement and short-term discharge. However, only one day later, the patient presented with a significant worsening of her symptoms and new onset of paresthesia. Since distally accentuated paresis of the left arm also occurred within a very short period of time, a cerebral MRI examination was performed. This revealed an extensive CVST. Due to the extensive CVST and progressive worsening of symptoms, mechanical venous thrombectomy was discussed and performed on an interdisciplinary basis. Mechanical thrombectomy was successful and resulted in complete improvement of symptoms.The pathophysiological diagnosis is cerebrospinal fluid leak syndrome after unsuccessful lumbar puncture. According to the Monroe-Kellie doctrine, the loss of CSF leads to compensatory dilatation and venous stasis, which in combination can lead to venous insufficiency and promote prothrombotic conditions. Although the available data on the performance of venous thrombectomy suggest caution, there should always be sufficient discretion for individual decision making. As our experience shows, there is a chance of successful venous thrombectomy in the early phase of CVST.
Keywords: electroencephalography (EEG); MR-diffusion/perfusion; MR-imaging